KONDISI FISIK HABITAT TARSIUS (Tarsius dentatus) DI KAWASAN TAMAN NASIONAL LORE LINDU DISEKITAR DESA SUNGKU KECAMATAN KULAWI KABUPATEN SIGI - Nofrianti, Nofrianti; Sudhartono, Arief; Toknok, Bau (Universitas Tadulako, 2015)
Tarsier (tarsius dentatus) is an endemic species in Sulawesi Island, these animals have a strong dependence on the forest. The objective of this study was to identify the physical conditions (abiotic) of tarsier habitat focused on the altitude, air temperature, air humidity and slope. These data were collected by conducting surveys and observation of the purposive sampling plot that was located in tarsier habitat in Lore LIndu National Park area around the village of Sungku. Physical conditions of the tarsier habitat were descriptively analyzed from identification, observation, measurement and actual conditions in the field. The result would be then compared with the other tarsier habitats at LLNP in village of Kamarora, Palolo sub-district. The altitude discovered tarsier habitat at the village Sungku is at 702-861- m a.s.l. the air temperatures range 20,33°C-24,66°C and humidity in the morning, and afternoon and evening were 85,3%, 71% and 75,3% is respectively. The slope of tarsier habitat varied from steep up to very steep (25%-40%). Where as in Kamarora village, tarsier habitat was at an altitude of 694 m a.s.l., whit a slope of 10%, air temperature (20,77°C-27,1°C) and humidity (72,3%-82%). The tarsier nets were observed during the study were at the bamboo cluster and Ficus sp. Tree. Keywords: Tarsier, tarsius dentatus, Habitat, Lore Lindu National Park.